Review of phononic crystals and acoustic metamaterials - Chen, Qiqi; Zhang, Bo; Bai, Yutian; Wang, Liheng; M. R. M., Rejab (IOP Publishing, 2020)
As a new type of acoustic functional material, phononic crystal has great research value and application environment. It is a periodic structure of two or more elastic materials, which are derived from photonic crystals. The main research work on phononic crystals focuses on the two band gap formation mechanisms of Bragg scattering and local resonance, and some new methods of vibration reduction and noise reduction can be obtained by studying its banding mechanism. Similarly, a "metamaterial" has been proposed for the ability to achieve new vibration reduction and noise reduction, which is a composite structure or material with physical properties not available in natural materials. By analysing the acoustic metamaterials of various structures, in this work we can understand how to achieve vibration reduction and noise reduction under the local resonance mechanism.